PROTOYPE GERBANG LOGIKA ( AND, OR, NOT, NAND, NOR ) PADA LABORATORIUM ELEKTRONIKA STMIK ROYAL KISARAN - Helmi Fauzi Siregar; Ikhsan Parinduri (Universitas Asahan, 2017)
Abstract - Logic gate prototype aims to meet the needs and smoothness of the teaching and learning process in one of the digital circuit lecture materials. Proof of the logic of OR, AND, NOT, NOR, and NAND gates. The working principle of logic gate prototype is working based on input logic including 0 and 1. For AND logic gates are input multiplication gates consisting of (0,0, 0,1, 1,0, 1,1) and output consists of 1 for high (1) and 3 for low (0). For OR gate is the input sum gate consists of (0,0, 0,1, 1,0, 1,1) and the output consists of 3 high (1) and 1 low (0). For the NAND gate is the logic inverting gate of the AND input gate consisting of (0,0, 0,1, 1,0, 1,1) and the output consists of 3 high (1) and 1 low (0). For NOR input logic gate consists of (0,0, 0,1, 1,0, 1,1) and the output consists of 1 for high (1) and 3 for low (0). For the NOT gate is the inverse gate with input (1, 0) and the output consists of (0,1). Keywords - Logic Gate, Prototype, OR, AND, NOT, NOR, NAND